Modification of Chitosan by Zincke Reaction: Synthesis of a Novel Polycationic Chitosan-Pyridinium Derivative - Gonçalves,Fernanda J. (2019)
Chitosan is a biodegradable aminopolysaccharide produced by deacetylation of acetamide groups of chitin, one of the most abundant organic materials in nature. Many different types of organic reactions have been described to modify the functional groups of chitosan and produce materials with applications in a large number of areas. However, the Zincke reaction, an old method which is commonly used to convert primary amine in pyridinium salts, has not been reported to transform the chitosan amino group at C-2 position in glucosamine units. In this paper, our efforts are described to carry out this reaction, employing different conditions to covalently anchor pyridinium salts on the polymer surface. Optimized synthesis conditions using water/ethanol as solvent, triethylamine and Zincke salt excess yielded a novel polycationic chitosan-pyridinium derivative with a weight gain of 52% after 48 h of reaction. The modified biopolymer is water insoluble and exhibits a high degree of chemical modification. The 13C solid state nuclear magnetic resonance (SS-NMR) spectrum of chitosan-pyridinium derivative showed signals at 147.0, 142.0 and 129.0 ppm, attributed to aromatic carbons, confirming the presence of a quaternary pyridinium ring directly attached to the biopolymer. The Zincke reaction was employed for the first time to modify the chitosan backbone.